Analysis of the Influence Compensation, Employee Engagement and Employee Welfare on Work Productivity in the Chemical Industry - Karyono, Karyono; Mirda Santi, Neta; Ramadhani, Aldi; Kurniawati, Nia; Nely Syahadah, Dewi; Sestri Goestjahjanti, Francisca; Winanti, Winanti; Ngadiyono, Ngadiyono; Ferdiyatmoko Cahya Kumoro, Dwi (International Journal of Innovation Research in Education, Technology and Management, 2024)
This research aims to analyze the influence of compensation, employee engagement and employee welfare on work productivity in the chemical industry. This research is motivated by the importance of increasing employee work productivity to maintain competitiveness amidst increasingly fierce global competition and ever-changing market demands. With research variables, the Influence of Competence (X1), Employee Engagement (X2) and Employee Welfare (X3) on Work Productivity (Y) in the chemical industry. to employees in the Synthetic Resin production section. The method used is a quantitative method, the population of this research was carried out on production employees totaling 95 people who were used as samples. The sampling technique uses Slovin samples. Data were collected using a questionnaire with a Likert scale, namely asking respondents for statements regarding the respondent's level of agreement with the questionnaire statements. The data obtained was analyzed using multiple linear regression techniques to identify the relationship and influence of the three dependent variables on work productivity. The research results can be seen from the multiple correlation level value of 0.801, this shows that the correlation level has a very strong influence. The coefficient of determination value is 0.651, meaning that the variables Compensation, Employee Engagement and Employee Welfare on Work Productivity in the Chemical Industry are 65.1% and the remaining 34.9% is influenced by other variables not examined in this research. Meanwhile, the results of simultaneous hypothesis testing show a significant effect because Fcount > Ftable (56,578>3.10)